Faktor - Faktor yang dapat Mempengaruhi Efektivitas Sistem Informasi Akuntansi - Fitri Sahidah; Trie Sartika Pratiwi (Equivalent : Journal of Economic, Accounting and Management, 2024)
Abstract : This research aims to examine the influence of accounting information technology, human resource competence, and user goals on the effectiveness of accounting information systems. The research employs a quantitative method, utilizing primary data obtained through the distribution of questionnaires to permanent employees of PT PLN (Persero) WS2JB who utilize SAP in the financial sector. The sample selection follows a purposive sampling method, with a total of 51 participants. Data analysis is conducted using Statistical Product and Service Solution (SPSS) version 25. The findings of this research indicate that both the use of information technology and human resource competence have a significant impact on the effectiveness of the accounting information system. However, it is noteworthy that user goals do not demonstrate any effect on the effectiveness of the accounting information system. Abstrak : Penelitian ini bertujuan untuk meneliti pengaruh pemanfaatan teknologi informasi akuntansi, kompetensi sumber daya manusia, dan kepuasan pengguna terhadap efektivitas sistem informasi akuntansi. Metode yang digunakan dalam penelitian ini adalah metode kuantitatif. Jenis data yang digunakan adalah data primer dengan menyebarkan kuisioner kepada karyawan tetap PT PLN (Persero) WS2JB yang menggunakan SAP di bidang keuangan Sampel pada penelitian ini diambil dengan menggunakan metode purposive sampling dengan total sampel sebanyak 51 orang. Teknik analisis data pada penelitian menggunakan Statistical Product and Service Solution (SPSS) versi 25. Penelitian ini menunjukkan bahwa pemanfaatan teknologi informasi dan kompetensi sumber daya manusia mempengaruhi efektivitas sistem informasi akuntasi, sedangkan kepuasan pengguna tidak berpengaruh terhadap efektivitas sistem informasi akuntansi.